Brief Report: Adults with Mild Autism Spectrum Disorders (ASD): Scores on the Autism Spectrum Quotient (AQ) and Comorbid Psychopathology - Ketelaars, Cees (Springer US, 2007)
While knowledge about symptom presentation of adults with mild ASD, including comorbid psychopathology, is limited, referral of adults with suspected mild PDD is increasing. We report on pilot research investigating whether patients diagnosed with mild ASD (n = 15) and patients who were not diagnosed with ASD (n = 21) differed in terms of (a) AQ scores and (b) Axis I and II disorders, assessed by the SCAN and the IPDE. Additionally, AQ scores were compared with those from non-ASD patients referred to a general outpatient clinic (n = 369). The results showed very few differences between ASD patients and non-ASD patients. Self-report may not differentiate mild ASD patients from non-ASD patients and Axis I and II disorders seem equally prevalent among these two groups.